Influence of UGT2B7, CYP3A4, and OPRM1 Gene Polymorphisms on Transdermal Buprenorphine Pain Control in Patients with Critical Lower Limb Ischemia Awaiting Revascularization. Issue 7 (26th September 2015) - Blanco, Francisco; Muriel, Clemente; Labrador, Jorge; Gonzalez‐Porras, Jose R.; Gonzalez‐Sarmiento, Rogelio; Lozano, Francisco S.
Abstract: Background: Pain control in critical limb ischemia (CLI) varies considerably between individuals. Objective: To evaluate pharmacogenetically the response to transdermal buprenorphine (BUP‐TTS) in patients with CLI who are awaiting revascularization. Methods: One hundred and seven patients with CLI were treated with BUP‐TTS. The following were analyzed: (1) pain perception (visual analog scale (VAS) before and 4 days after treatment) and (2) genetics: glucuronosyltransferase (UGT2B7), cytochrome (CYP3A4), and μ‐opioid receptor (OPRM1) gene polymorphisms. Results: Ninety‐three patients completed the study. The VAS score by the fourth day of analgesia dropped from 6.82 to 3.38 ( P < 0.05). The analgesic response to BUP‐TTS was greater in men than in women ( P = 0.019). Patients who were AA homozygotes for the CYP3A4 gene showed the best response to analgesic treatment ( P = 0.003). The combination of the CYP3A4 gene with UGT2B7 or OPRM1 was favorable to the effect of the CYP3A4 gene ( P = 0.045 and P = 0.026, respectively). The combination of UGT2B7 with OPRM1 was ineffective ( P = 0.648). The 3 polymorphisms together had no effect on response to treatment ( P = 0.461). Conclusions: BUP‐TTS is efficacious in the control of pain in patients with CLI. The homozygous AA carriers of the CYP3A4 gene respond better to treatment with BUP‐TTS.